Economic Approach to Valuing Information with Applications to Climate Information - Tatiana Borisova; Norman Breuer; Irina Grinberg (EDIS)
FE801, a 6-page illustrated fact sheet by Tatiana Borisova, Norman Breuer, and Irina Grinberg, gives a basic introduction to the economic approach to valuing information. Specifically, it discusses a way to evaluate the information in Florida climate forecasts in order to improve agriculture decisions and thereby produce more reliable economic outcomes. Includes references. Published by the UF Department of Food and Resource Economics, June 2009.